Inhibitive effect of some gemini surfactants as corrosion inhibitors for mild steel in acetic acid media - Ansari F.A.; Quraishi M.A. (My University, 2025)
A number of gemini surfactants from the series of 1,2-alkane-bis-(ethyl ammonium bromide) were synthesized and their inhibitive effects on mild steel corrosion in acetic acid were evaluated by weight loss and electrochemical polarization measurements. Their critical micelle concentrations at equilibrium in water at 30°C were also determined. The results obtained revealed that all the studied gemini surfactants are effective in reducing corrosion of mild steel in acetic acid media. The adsorption of the inhibitors on the mild steel surface obeys Langmuir's adsorption isotherm. The thermodynamic parameters of adsorption revealed a strong interaction between the inhibitors and the corroding mild steel surface. The influence of inhibitor concentration, solution temperature, immersion time and acid concentration on the corrosion of mild steel has also been investigated. © King Fahd University of Petroleum and Minerals 2010.